The impact of teams on output, quality and downtime: an empirical analysis using individual panel data - Derek C. Jones; Takao Kato (Institute for the Study of Labor (IZA), 2007)
To investigate the size and the timing of the direct impact of participatory arrangements on business performance, we assemble and analyze extraordinary daily data - for rejection, production and downtime rates for all operators in a single plant during a 35 month period, more than 77,000 observations. Consistent with core hypotheses that employee involvement enhances productivity and quality through mechanisms including employees becoming better motivated, more informed and paying greater attention to product details, we find that membership in offline teams: (i) initially enhances individual productivity by about 3%; (ii) and lowers rejection rates by about 27%. We also find that: (iii) these improvements are dissipated, typically at 10 to 16% per 100 days in a team; (iv) while initially teams lead to more downtime, these costs diminish over time; (v) the performance-enhancing effects of team membership are generally greater and more long-lasting for team members who are solicited by management; (vi) similar relationships exist for more educated team members. These findings square with diverse hypotheses concerning predicted gains from complementarities in organizational design, the benefits that flow from management solicitation and enhanced education, but are inconsistent with hypotheses based on Hawthorne effects.
Keywords: 650; Gruppenarbeit; Leistungsmotivation; Arbeitsproduktivität; Produktqualität; Fehlzeit; USA